Bifurcation of Travelling Wave Solutions of the Generalized Zakharov Equation - Masoud Mosaddeghi (Journal of Applied Mathematics)
By using bifurcation theory of planar ordinary differential equations all different bounded travelling wave solutions of the generalized Zakharov equation are classified in to different parametric regions. In each of these parametric regions the exact explicit parametric representation of all solitary, kink (antikink), and periodic wave solutions as well as their numerical simulation and their corresponding phase portraits are obtained.